An unusual abdominal pain in the emergency department: a delayed presentation of diaphragmatic injury - Ciro Paolillo; Valentina Siragusa (Emergency Care Journal, 2016)
We present a case of delayed traumatic diaphragma rupture. The patient complained of a vague abdominal pain and left shoulder pain. Only the relevance of a remote trauma aroused the suspicion.